Formation of Multi-coatings on Nickel: Structure, Phase formation, Physical and Chemical Properties - V.G. Hignjak; O.E. Datsiuk; N.A. Harchenko; Т.P. Hоvоrun; H.A. Holubovska; N.I. Shumakova (Журнал нано- та електронної фізики)
Methods of aluminum-silicon and titanium-aluminum coatings of nickel in a mixture of metal powders, aluminum oxide Al2O3 and ammonium chloride NH4Cl were proposed. Phase and chemical composition, structure, microhardness of multicomponent diffusion coatings involving aluminum and silicon, titanium and aluminum on nickel were established. It is shown that diffusion coatings consist of the compound zone and transition zone, which is a solid solution of saturating elements in nickel.